Evaluación de la participación ciudadana en el Gobierno Autónomo Descentralizado de la Parroquia Canuto del período 2014/2017. - Mero Chichanda, Gema Jennifer (2018)
The main objective of this research work was to evaluate the citizen participation at the Autonomous Decentralized Government of Canuto parish from 2014-2017 to improve its application, where several activities were carried out using methods, techniques and types of research. Relevant topics of the research topic were consulted, as well as an analysis of the legal framework and the parochial regulations that govern the existing mechanisms to promote the Civic Participation of the parish, mechanisms that are based on the Constitution of the Republic of Ecuador, the Organic Law of Citizen Participation, the Code of Democracy, the Citizen Participation Council Law, the Organic Code of Territorial Organization and the Organic Code of Public Finance Planning. In addition, the participation of the citizens in the decision making of the parochial GAD was valued, which helped to obtain relevant information for the development of this work. Applied the investigation of the citizen participation in the parish Canuto it is evident that there are certain shortcomings, since great part of the population ignores the mechanisms of participation. It is concluded that with the inputs thrown the action plan was created, where inclusive strategies are designed that will help improve management within the institution, considering that citizen participation has a direct or indirect impact on the socioeconomic development.